Pedagogical model for the development of a sustainable lifestyle of a student in a cultural landscape - Demidova, Natalia Nikolaevna; Loshchilova, Anna Aleksandrovna; Vinokurova, Natalya Fedorovna; Zulkharnaeva, Anastasia Vasilievna; Martilova, Natalia Viktorovna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The article considers the eco-friendly lifestyle of a person in a cultural landscape as a prerequisite for sustainable development of a territory and a practical basis for creating a qualitatively new harmonious interaction between society and natural systems. The goal of the article is to theoretically substantiate, devise, and test a pedagogical model that would teach students a sustainable lifestyle in a cultural landscape. The methodological basis of the study is the coevolutionary subjective, activity, transdisciplinary, integral, situational, cultural, ecological, landscape, and environmental approaches, as well as some principles embodying them. Educational modeling and design were the key theoretical methods. The pedagogical model created combines the target, substantive, procedural, technological, productive, and evaluative components. Its practical use in schools proved to be effective regarding the formation of an eco-friendly lifestyle of students in the cultural landscape.